Kepuasan Pelanggan terhadap Pelayanan Pendidikan Berbasis Sistem Manajemen Mutu ISO 9001:2008 di Madrasah Ibtidaiyah se-Yogyakarta - Inggit Dyaning Wijayanti (Jurnal Pendidikan Madrasah, 2020)
This research aims to measure customer satisfaction towards ISO 9001:2008 quality management service. This study uses quantitative descriptive methods. The data sources used are student questionnaires and parents of MIN Jejeran and MIN Tempel students. The research model used is SERVQUAL using 5 dimensions namely (tangible, reliability, responsiveness, assurance, empathy). The results of the study at MIN Jejeran showed an average performance level of 3.90 (satisfied) and expectations of 4.60 (important) and an average gap value of -0.70 (satisfied category, due to gap of < -1) with a conformity rate of 84.71%. MIN Jejeran customer satisfaction level belongs to the satisfactory category. While the results of the study at MIN Tempel showed an average performance level of 3.65 (satisfied) and expectations of 4.64 (important), and an average gap value of -0.99 (satisfied category, due to gap of < -1) with a conformity rate of 78.55%. The level of customer satisfaction towards MIN Tempel service is satisfactory.